Dose –Response Analysis of Moringa oleifera (From Jalu City, Libya) Leaf Aqueous Extracts on Mitotic Indices and Chromosomal Aberrations in Allium cepa Bioassay - El shatshat, Salem; Fawzia Al Jazwi; Salma Hamad Idris (AlQalam Journal of Medical and Applied Sciences, 2025)
This study used the Allium cepa bioassay to investigate the cytotoxicity and genotoxicity effects of water leaf extracts from Moringa trees, a plant recently introduced to Libya. Root tips were treated with different extract concentrations (0%, 2.5%, 5%, 10%) for various durations. The findings revealed a complex dual effect. Higher concentrations and longer exposure times significantly stimulated cell division, dramatically increasing the mitotic index by over threefold in some cases. However, the extracts were also clastogenic, including chromosomal abnormalities like sticky chromosomes and C-metaphase. Notably, the highest percentage of abnormal cells (25.65%) occurred at a moderate concentration (5%) after only 3 hours, suggesting potent genotoxicity at certain exposure levels. The results indicate that M. oleifera leaf extracts can act as both a mitotic stimulant and a genotoxic agent, with effects critically dependent on concentration in traditional medicinal use.